Corporate Social Responsibility (CSR) and Tax Avoidance (TA) in Indonesia : Moderated Audit Committee Characteristics - Wulandari, Annisa; Fanani, Zaenal (Accounting Analysis Journal, 2024)
Purpose: The study aims to determine the effect of Corporate Social Responsibility (CSR) on Tax Avoidance (TA) whether they have substitution or complementary influences. In addition, the researcher wanted to investigate whether the characteristics of the audit committee can be moderated between Corporate Social Responsibility (CSR) and Tax Avoidance (TA). Method: The study analyzes non-financial companies in Indonesia listed on OSIRIS in 2017 – 2021. The purposive sampling method produced 399 research samples. Researchers used regression panel data to determine the effect of Corporate Social Responsibility (CSR) on Tax Avoidance (TA) and the effect of audit committee moderation. Findings: The results showed that Corporate Social Responsibility (CSR) has a significant positive influence on Tax Avoidance (TA) while Audit Committee Size (ACZ) and Female Members in Audit Committee (FMAC) have an insignificant influence. Novelty: The research will add literature related to the influence of Corporate Social Responsibility (CSR) on Tax Avoidance (TA) by providing an overview of how company management in Indonesia utilizes Corporate Social Responsibility (CSR). Whether as a philanthropic activity or used to make up an unethical act such as Tax Avoidance (TA). This study also provides a new picture by providing a moderating effect characteristic of the audit committee.